(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background:Viruses are among the most common causes of opportunistic infections after transplantation. The risk for viral infection is a function of the specific virus encountered and the intensity of immune suppression used to prevent graft rejection.Epstein-Barr virus infection has also been implicated as co-factor in acute and chronic rejection syndromes. Objective:Detection of Epstein-Barr viremia in renal transplant recipients. Methods: Fifty seven (57) renal transplant recipients were enrolled in this study. Plasma samples were taken from all renal transplant subjects. Screening of Epstein-Barr virus was first done by serology viamono spot test, then, viral DNA of Epstein-Barr viruswas extracted from 200 µl plasma samples and Epstein-Barr virus DNA was detected and measured by Taqman quantitative real-time PCR. Results:19/57 (33 %) of renal transplant subjects had Epstein-Barr virus viremia and the viral load ranged from 7100 to 16.165 copies/ml. Serology of all RT subjects showed negative heterophil antibody except for one patient had positive hetrophil antibody. Conclusion:The current study showed that Epstein-Barr virus might be considered as an important cause of renal impairment and allograft loss in renaltransplant subjects. And Epstein-Barr virus seems associated with post transplantation renal impairment and/or kidney rejection. Real-time PCR is a very sensitive and specific method for the detection of Epstein-Barr viremia in renal transplant subjects. Key words:Epstein-Barr virus, Renal transplantation, real-time PCR